2011
DOI: 10.1155/2011/657516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanometer Ce0.75Zr0.25O2Powders by Solid-State Chemical Reaction Method

Abstract: The nanostructure Ce0.75Zr0.25O2powders have been successfully synthesized by using the mechanically activated solid-state chemical reaction method for the first time, with Ce2(CO)3, ZrOCl2⋅8H2O, and H2C2O4⋅2H2O as raw materials. The structure and morphology of Ce0.75Zr0.25O2powders were characterized to be in the single cubic phase and spherical shape via X-ray powder diffraction, transmission electron microscopy, X-ray Photoelectron Spectrometer, and BET surface area testing technique. The average size of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Solid-state reaction method overcame these disadvantages, but consumed large amount of energy. Mechanical activation solid-state chemical reaction method not only decreased the synthesis temperature but also did not generate waste liquid [14].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state reaction method overcame these disadvantages, but consumed large amount of energy. Mechanical activation solid-state chemical reaction method not only decreased the synthesis temperature but also did not generate waste liquid [14].…”
Section: Introductionmentioning
confidence: 99%
“…Often, a liquid component is added to the mill. For example, Zheng et al [155], starting from ZrOCl 2 •2H 2 O, Ce 2 (CO 3 ) 3 and H 2 C 2 O 4 •2H 2 O, added various surfactants to ground substrates. The largest specific surface areas (>80 m 2 /g) of Zr x Ce 1−x O 2−y nanoparticles were obtained using neutral surfactants and these carriers were the best for the subsequent deposition-precipitation of Pd and Rh in the production of TWC car catalysts.…”
Section: Synthesis Of the Ceria-based Nanoparticlesmentioning
confidence: 99%
“…11 Trasobares et al reported that zirconia−ceria mixed oxide nanomaterials are of interest as catalysts in a variety of chemical transformations in the area of environmental protection. 17 The synthesis and characterization of nanometer Ce 0.75 Zr 0.25 O 2 powders by a solid-state chemical reaction method was reported by Zheng et al 18 However, there have been no reports on the use of phosphomolybdic acid supported on ZrO 2 −CeO 2 as the catalyst for the solvent-free oxidation of benzyl alcohol. The present article reports for the first time the surface and textural characterization of phosphomolybdic acid stabilized zirconia−ceria mixed oxide.…”
Section: Introductionmentioning
confidence: 99%